(untitled) (Ius Novum, 2020)
The emergence of the coronavirus proves that Europe is essentially one organism, and the considerable mobility of its inhabitants indicates that health protection should be thought of in terms of the entire continent or even globally. Therefore, the health policy was rightly considered in the Treaty on the Functioning of the European Union, in Article 168, to be a separate policy of the European Union. However, it is also supported by later quite detailed regulations. These regulations stress the importance of vaccination for the protection of public health, and the need to provide information on infectious diseases. An epidemiological surveillance and control network has also been established in the EU. It was also noted that accelerated marketing of medicinal products, including vaccines, is possible even when some clinical data are not available. Vaccines were considered to be medicinal products that are subject to regulations and procedures adopted at the European Union level. It was pointed out that the whole society should be aware of the value of vaccination. It is necessary, in the face of false and inaccurate information, to conduct information campaigns on the dangers of infectious diseases that are preventable by vaccination. Attention was also paid to the negative effects of anti-vaccination movements, stating that as a result of their actions a significant part of the population in the EU countries evades vaccination.